Effects of Combined Cataract Surgery on Outcomes of Descemet's Membrane Endothelial Keratoplasty: A Systematic Review and Meta-Analysis - Tey, Kai Yuan; Tan, Sarah Yingli; Ting, Darren S. J.; Mehta, Jodhbir S.; Ang, Marcus (Frontiers in Medicine, 2022)
Objective: A systematic review and meta-analysis of literature-to-date regarding the effects of combined cataract surgery on outcomes of DMEK. Methods: Multiple electronic databases were searched, including Cochrane Library databases, PubMed, Web of Science, and ClinicalTrials.gov. The final search was updated on 1st April 2020. We included randomized controlled trials (RCTs), non-randomized studies (NRS) and large case series (≥25 eyes) of DMEK (pseudophakic/phakic) and ‘triple DMEK’. A total of 32 studies were included in this study. Meta-analyses were done with risk differences (RD) computed for dichotomous data and the mean difference (MD) for continuous data via random-effects model. Primary outcome measure: postoperative re-bubbling rate; secondary outcome measures: complete/partial graft detachment rate, best-corrected visual acuity (BCVA), endothelial cell loss (ECL), primary graft failure, and cystoid macular edema (CMO). Results: A total of 9649 eyes were included in this review. Based on NRS, DMEK alone demonstrated a significantly lower postoperative re-bubbling rate when compared to triple DMEK (RD = -0.07; 95% CI = -0.11 to -0.02; p=0.002). Triple DMEK demonstrated a better BCVA at 1-month postoperative than DMEK alone (MD 0.10 logMAR; 95% CI: 0.07 to 0.13; p<0.001), though not statistically significant at 3-6 months postoperative (MD 0.07 logMAR; 95% CI: -0.01 to 0.15; p=0.08). There was no significant difference in the ECL, graft failures and CMO at all evaluated timepoint between the two groups (all p>0.05). Conclusion: Our review suggests that DMEK had a lower rate of postoperative re-bubbling compared to ’triple DMEK’ (low-quality evidence), with comparable visual outcome and graft survival rate at 6 months postoperative. High-quality RCTs specifically studying the outcomes of combined versus staged DMEK are still warranted.